Mucosectomy impairs ileal microcirculation and results in flap contraction after experimental ileocystoplasty. Issue 1 (February 2017) - Cervellione, Raimondo M.; Hajnal, Daniel; Varga, Gabreilla; Rakoczy, George; Kaszaki, Jozsef; Keene, David; Goyal, Anju; Dickson, Alan; Cserni, Tamas
Summary: Introduction: Bladder augmentation with demucosalized ileal flap is a promising alternative approach for mucus free bladder augmentation; however, the contraction of the flap is still a major concern. It has been hypothesized that mucosectomy causes ischemic damage, but no direct histological evidence has been found and attention is now focused on the urothelium cover to prevent the exposure of the denuded surface to urine or the use of balloons to keep the flaps distended. Objective: Our aim was to study the effect of mucosectomy on the microcirculation of ileal flaps during reverse clam ileocystoplasty using direct intraoperative imaging of the ileum. Since the omentum is successfully used to revascularize ischemic tissue, we also examined whether omentopexy can prevent contraction. Study design: Clam ileocystoplasty was performed in anesthetized minipigs with seromuscular ( n  = 3), seromusculo-submucosal ( n  = 3) reverse demucosalized ileal flaps. The velocity of the circulating red blood cells (RBCV) and the perfusion rate (PR) was measured with intravital videomicroscopy (Cytoscan A/R, Cytometrics, Philadelphia, PA, USA) before and after mucosectomy and the denuded surface of the ileum was covered with omentum after the reverse augmentation was complete (Figure). Animals were sacrificed after 8 weeks and the ileal flap dimensions were measured. Results: Significant reduction in RBCV and PR was detected after mucosectomy in both groups; however, no sign of acute flap necrosis or bladder perforation was seen. The omentum was found firmly attached to the ileal flaps, but contraction of the flaps was significant in both groups. Conclusion: The disturbance in the microcirculation observed after mucosectomy may be responsible for flap contraction in ileocystoplasty with demucosalized ileum. Omentopexy did not help to prevent contraction. Discussion: Contraction of demucosalized intestinal flaps used for bladder augmentation has been frequently reported. This study provides direct evidence the first time for severely compromised microcirculation of the ileal flaps after mucosectomy. Limitation of the study is the relative low number of animals sacrificed. Figure Augmented bladder with reverse sero-musculo-submucosal ileal flap covered with the omentum.